Słuchowo-językowe funkcjonowanie dzieci bilateralnie zaimplantowanych wszczepem ślimakowym w trybie sekwencyjnym, doniesienie wstępne - Magierska-Krzysztoń, Magdalena (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Severe hearing damage in the prenatal period or when the baby is born is a disability that significantly impairs the correct functioning in the society of hearing people. A particularly perceptible consequence of severe hearing impairment is the lack or significant delay in the development of speech and language acquisition. Thanks to the use of cochlear implants, the Program Chirurgicznego Leczenia Głuchoty Metodą Wszczepów Ślimakowych [Program of Surgical Treatment of Deafness With the Method of Cochlear Implantation] allows children with perceptive deafness for the access to speech sounds through the auditory pathway. It gives them an opportunity to develop speech and language and in the future – the ability to satisfactorily communicate with other people. The study covered 54 born-deaf children, bilaterally implanted in the sequential mode. The implantation was performed at the Department of Otolaryngology and Laryngological Oncology of the Poznan University of Medical Sciences. The results indicate a constant, dynamic increase of auditory and linguistic-communication skills in the examined group.